The EU and the Arab Spring: between spectatorship and actorness - Schumacher, T. (Insight Turkey, 2011)
Throughout the first seven months of the Arab Spring, starting with the self-immolation of Mohammed Bouazizi in the Tunisian town of Sidi Bouzid on December 17, 2010, the EU clearly revealed itself as both an actor and spectator by resorting to both activism and passivism in a seemingly erratic fashion. Against this background and based on the EU’s recently adopted Partnership for Democracy and Shared Prosperity with the Southern Mediterranean, this article aims at understanding this dualism more precisely and shedding some light on the EU’s rather anachronistic foreign policy behavior in the Middle East and North Africa (MENA) in recent months. The article identifies five dichotomies, all of which contribute to the situation in which the EU continues to be torn between being a relevant political actor in the MENA region and a simple spectator that continues to be overwhelmed by local and regional political developments.